Sol gel dielectrics for organic field effect transistors : investigations of device performance enhancement, molecular organization and interfacial chemistry effects - Cahyadi, Tommy (2008)
The interfacial interactions between semiconductors and gate dielectrics have a profound influence on the device characteristics of field effect transistors (FETs). This thesis reports on the concept of introducing sol-gel silica as solution-processable inorganic gate dielectric with improved OFETs performance. The smoother film surfaces of sol-gel silica (~1.9 Å root-mean-square) and low surface energy (water contact angle of ~75°) have been shown to allow effective modification of bottom layer topography without being limited by the chemistry required for self-assembled monolayer (SAM) functionalization, while simultaneously fine-tuning the dielectric surface, thus resulting in planarization of dielectric surface roughness in stacked gate dielectric applications.